Research and optimization on the sensing algorithm for 6G integrated sensing and communication network - Xiaoyun WANG; Xiaozhou ZHANG; Liang MA; Yajuan WANG; Mengting LOU; Tao JIANG; Jing JIN; Qixing WANG; Guangyi LIU (Tongxin xuebao)
High-precision sensing is one of the basic capabilities of 6G mobile communication system to fulfill the demands of many application scenarios in the future, and the integrated design of sensing and communication (ISAC) is an important direction of 6G research.The works on ISAC mainly focus on improving the sensing performance.However, besides high sensing accuracy, 6G ISAC network still has a high communication rate requirement.Therefore, joint analysis and design of communication and sensing is necessary.First, three classic sensing algorithms were introduced that could achieve multi-target ranging and speed measurement, and the algorithms were analyzed from three aspects: sensing accuracy, communication performance and computational complexity.It is shown that the optimal sensing accuracy, sensing capacity and communication rate could not be achieved at the same time by using either one algorithm.Second, combined with the characteristics of different sensing algorithms, an adaptive sensing algorithm was proposed that the receiver selected the appropriate sensing algorithm according to the measured receive signal-to-interference-plus-noise ratio to realize the joint optimization of sensing and communication performance.Finally, the link-level simulation was carried out to verify that the proposed algorithm can obtain better sensing accuracy and communication capacity than any single algorithm.